Optimum light wavelength and light intensity for the survival and growth of juvenile of African catfish, Clarias gariepinus - Muhammad Firdaus bin Sallehudin (Kulliyyah of Science, International Islamic University Malaysia, 2017)
The survival and growth rates of African catfish (Clarias gariepinus) were reported to be affected by light conditions. Most of the previous studies on African catfish had focused on the effects of light intensities, but the effects of light wavelengths are still poorly understood. Thus, the objectives of this study were to investigate the effect of different light wavelengths and light intensities on African catfish juveniles. In this study, three experiments were conducted which are rearing, behaviour and cortisol experiment. For fish rearing experiment, African catfish juveniles were reared for 14 days under five different light wavelengths (white, blue, green, yellow, and red) and three different light intensities (1.40, 0.014, and 0.0014 µmoles/m²/s) to determine their survival rates, growth rates, and production index. For the second experiment, the behaviour of the juveniles under different light and light wavelengths and light intensities were observed. Two types of behaviour (fish resting activities and fish biting activities) were analysed to determine the level of fish aggressiveness. For the third experiment, the cortisol levels of the juveniles were analysed using ELISA kit. The purpose of this experiment is to determine the stress level of the fish under different light conditions. Regarding the effects of light wavelengths, the juvenile showed the highest growth rates when reared under yellow light wavelength. Besides that, the lowest biting activities were observed when the juveniles reared under yellow light wavelength. Although the juveniles' cortisol level under yellow light wavelengths was slightly higher than the juveniles reared under blue light wavelength, the increase in cortisol level were able to promote the juveniles' feed intake, thus increasing their growth rates. Regarding light intensities, the results showed that light intensity had significant effect on the behaviour and the cortisol level of the juveniles. The juveniles reared under light intensity of 0.0014 µmoles/m²/s has lower aggressive behaviour and cortisol level than the juveniles reared under 1.40 µmoles/m²/s. However, there was an interaction between light wavelengths and light intensities. The juveniles reared under white light wavelength showed the highest growth rates at a light intensity of 0.0014 µmoles/m²/s, in contrast, the juveniles reared under yellow light wavelength showed the highest growth rates at a light intensity of 1.40 µmoles/m²/s. These indicate the effect of light wavelengths on the juveniles was differed under different light intensities. Among fifteen light conditions experimented, the juveniles showed the highest growth rates and production index and the lowest aggressive behaviour when reared under yellow light wavelength of 1.40 µmoles/m²/s. Therefore, rearing of African catfish juveniles under yellow light wavelength of 1.40 µmoles/m²/s is recommended.